Entrepreneurial Entropy: A Resource Exhaustion Theory of Firm Failure From Entrepreneurial Orientation - Gali, Nazha; Hughes, Mathew (Mat); Morgan, Robert E.; Wang, Catherine L. (Entrepreneurship Theory and Practice, 2024)
Entrepreneurial orientation (EO) can generate substantial gains and losses, exhausting firm resources and straining a firm’s ability to sustain its activities. We develop and test a resource exhaustion theory of firm failure, conceptualizing conditions under which EO increases the risk of firm failure by generating unsustainable amounts of entrepreneurial entropy. Using panel data on 804 large U.S. high-technology firms over 18 years, we find that EO increases the risk of firm failure, which is mediated by the lack of organizational resource slack. An abrupt change in EO increases the risk of firm failure, especially among underperforming firms.